Fishery, biology and population dynamics of Nemipterus japonicus (Bloch) off Visakhapatnam - Rajkumar, U; Rao, K Narayana; Kingsly, H Jose (Indian Journal of Fisheries, 2011)
Threadfin breams formed 9% of the total small trawler catches of Visakhapatnam, Nemipterus mesoprion and N. japonicus being the dominant species. The estimated growth parameters for N. japonicus are L = 340 mmn and K = 0.52 year-1. Size at first maturity is estimated as 128 mm. The species spawns during July to April with a peak in September. The mortality rate Z, F and M were 3.52, 2.41 and 1.11 respectively.